Raquel Raso - Study of the hydrogen production by aqueous phase reforming of glycerol over Ni-based catalysts - Raso, Raquel (Jornada de Jóvenes Investigadores del I3A, 2022)
Study of the hydrogen production by aqueous phase reforming of glycerol over Ni-based catalysts